Analisis Implementasi Kebijakan Pajak Progresif Kendaraan Bermotor Pada Samsat Cinere Depok II Tahun 2018-2020 - Maharani Octari Putri; Jiwa Pribadi (Jurnal Ilmu Administrasi Publik, 2021)
The purpose of this study is to analyze the Progressive  Tax policy implementation  motor vehicles on the One-stop Administration Service Office of Cinere Depok  II. This research discusses three problems: the Progressive  Tax policy implementation  motor vehic les, the obstacle factors, and solutions to solve the obstacles. Descriptive  qualitative method is used as the method of this research, and the data is collected by interview  method to several parties. According to the result of the study, from 2018 to 2020, the policy implementation  of Progressive  Tax motor vehicles in the One-stop Administration Service Office of Cinere Depok II is considered not going well from some aspects, and, there are still some obstacles to handle.  There will be a problem when a taxpayer  does not report  the vehicles they sell because they forget to block or protect the sold vehicles, or problems caused by the lack of awareness  of the people in paying the Progressive Tax.